Predictors of abdominal obesity and high susceptibility of cardiometabolic risk to its increments among Turkish women:: a prospective population-based study - Onat, Altan; Sari, Ibrahim; Hergenc, Gulay; Yazici, Mehmet; Uyarel, Huseyin; Can, Gunay; Sansoy, Vedat (W B SAUNDERS CO-ELSEVIER INC, 2007)
To investigate determinants of abdominal obesity and its metabolic and clinical consequences relative to its degree in women, a prospective evaluation of 1682 female participants (aged 28-79 years at baseline), representative of Turkey's women, was performed. For components of metabolic syndrome (MS), criteria of National Cholesterol Education Program guidelines were adopted, modified for cut point of 91 cm or greater for abdominal obesity and less than 45 mg/dL for low high-density lipoprotein (HDL) cholesterol. Fasting insulin and C-reactive protein concentrations and (inversely) smoking more than 10 cigarettes daily were significant predictors of newly developed abdominal obesity at a follow-up of mean 5.9 years. In the prediction of high triglyceride-low HDL dyslipidemia, elevated blood pressure (BP) or MS and doubling of baseline fasting insulin level contributed approximately 25% to the hazard ratio (HR), whereas waist circumference exhibited independent HRs of 1.30, 1.62, and 2.22, respectively. Waist girth (or body mass index) quartiles was the major predictor (HR, 1.72) of diabetes mellitus (DM), followed by physical inactivity and total cholesterol and insulin levels, all independent of each other. Waist girth quartiles in women conferred excess risk of incident coronary heart disease from quartile II onward, independent of age, DM, and elevated BP. Fasting insulin and C-reactive protein levels and (inversely) heavy smoking are main predictors in Turkish women of abdominal obesity. Across waist girth quartiles, multiadjusted relative risks for dyslipidemia, elevated BP, MS, and coronary heart disease rise sharply and asymptotically from quartile II (>= 83 cm) onward, whereas risk of DM emerges in the top quartile. A waist girth of 83 cm or greater should be regarded as abdominal obesity among Turkish women. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: C-REACTIVE PROTEIN; METABOLIC SYNDROME; WAIST CIRCUMFERENCE; INSULIN-RESISTANCE; CARDIOVASCULAR RISK; DIABETES-MELLITUS; LIFE-STYLE; ASSOCIATION; ATHEROSCLEROSIS; IDENTIFICATION; Endocrinology & Metabolism